2014
DOI: 10.1186/1471-2407-14-449
|View full text |Cite
|
Sign up to set email alerts
|

The bacterial protein toxin, cytotoxic necrotizing factor 1 (CNF1) provides long-term survival in a murine glioma model

Abstract: BackgroundGlioblastomas are largely unresponsive to all available treatments and there is therefore an urgent need for novel therapeutics. Here we have probed the antineoplastic effects of a bacterial protein toxin, the cytotoxic necrotizing factor 1 (CNF1), in the syngenic GL261 glioma cell model. CNF1 produces a long-lasting activation of Rho GTPases, with consequent blockade of cytodieresis in proliferating cells and promotion of neuron health and plasticity.MethodsWe have tested the antiproliferative effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…In vitro and in vivo assays showed that CNF1 triggers molecular and morphological hallmarks of senescence ( Figure 2 ), which eventually lead murine and human glioma cells to death. Specifically, CNF1-treated glioma cells show an overexpression of p21 and p16, while FoxG1 is downregulated; these markers point to an activation of the senescence process, that was also confirmed by β-galactosidase staining ( Figure 2 ) [ 62 , 63 ].…”
Section: Cnf1 Action In Glioma: Functional Sparing Of Peritumoral mentioning
confidence: 80%
See 2 more Smart Citations
“…In vitro and in vivo assays showed that CNF1 triggers molecular and morphological hallmarks of senescence ( Figure 2 ), which eventually lead murine and human glioma cells to death. Specifically, CNF1-treated glioma cells show an overexpression of p21 and p16, while FoxG1 is downregulated; these markers point to an activation of the senescence process, that was also confirmed by β-galactosidase staining ( Figure 2 ) [ 62 , 63 ].…”
Section: Cnf1 Action In Glioma: Functional Sparing Of Peritumoral mentioning
confidence: 80%
“…We found that CNF1 impairs motility and proliferation of both murine and human glioma cells causing their death in 15 days [ 62 , 63 ]. In vitro and in vivo assays showed that CNF1 triggers molecular and morphological hallmarks of senescence ( Figure 2 ), which eventually lead murine and human glioma cells to death.…”
Section: Cnf1 Action In Glioma: Functional Sparing Of Peritumoral mentioning
confidence: 99%
See 1 more Smart Citation
“…Specificity of CNF1 action in photoreceptors may also result from a selective vulnerability: these metabolically very active cells are likely sensitive to dysregulation of intracellular signaling, so that continuous activation of Rho GTPase signaling and changes in cytoskeletal organization may lead to their degeneration. This interpretation is supported by the cytotoxic effects of CNF1 on proliferating cells such as glioma cells 33 . In addition, mutations in proteins involved in the dynamics of actin cytoskeleton lead to severe photoreceptor phenotypes and retinal blindness, as it is the case of ciliopathies including Usher syndrome 34 .…”
Section: Discussionmentioning
confidence: 81%
“…To induce glioma formation, C57BL/6 mice (12–14 weeks old) received a stereotaxically guided injection of 40,000 GL261 cells into the visual cortex (2 mm lateral to the midline and in correspondence with lambda) using fine glass micropipettes (tip diameter 40 μm) 16, 43 .…”
Section: Methodsmentioning
confidence: 99%